Introduction of Teachers Perspective on Instructional Strategies: Implemented at Early Childhood Years - Mumuni Thompson (Progress in Language, Literature and Education Research Vol. 8, 2024)
The study demonstrated the potentials that exist for the use of instructional strategies to complement the teachers" attempt to create constructive learning environments in early childhood settings. Instructional strategies contribute to effective teaching and learning in early childhood classrooms, which in turn, impacts children’s development in diverse ways. Even though previous research points to the significance of early childhood teachers’ practices that take into consideration the nature of children and how they learn, there is limited research regarding how instructional strategies impact children’s development in diverse ways. A multi-case-qualitative study approach was used in this study because there is a need to establish the differences regarding teachers" practices in Tata School and Kariba School sited in different socio-economic settings. One research question guided the study, namely, which instructional strategies do teachers use in a kindergarten classroom? Data used were semi-structured individual interviews pair-based interviews and field notes of classroom observations. Both within and across case interpretative analysis, as was used. The findings of this study revealed these teachers believed that instructional strategies impacted children’s development in different ways; they pointed to play-based instruction and integration as well as specific strategies such as picture-walk and think-pair-share that they believed to promote effective teaching and learning in kindergarten classrooms which in turn, enhanced and promoted children’s multiple intelligences in terms of socio-emotional, physical, cognitive and language development. The study established that insights of pre-service early childhood teachers into the appropriate use of both specific and generic instructional strategies regarding when and how to use each of them within the teaching and learning context have the potential to unearth children’s potential by situated the selection of instructional strategies within the context of the uniqueness that individual children bring to the teaching and learning context concerning interests, needs and potential.